15 THE HEAVY BURDEN OF SARS-COV-2 RELATED PNEUMONIA REQUIRING HIGH-OXYGEN FLOW. (15th December 2022) - Salvotti, Francesca; Scipione, Vittorio; Flamminio, Gigliola; Pastori, Antonella; Geroldi, Veronica; Volpe, Pietro; Borghi, Erika; Tosoni, Federico; Fusco, Elena Maria; Malerba, Paolo; Ferrari-toninelli, Giulia; De Ciuceis, Carolina; et al.
Abstract: Aim: there is evidence of significant clinical sequelae of COVID-19 that may impair both life length and its quality. Aim of this study was to assess the long-term consequences of moderate to severe SARS-CoV-2-related pneumonia in patients requiring high-flow oxygen treatment. Methods: This prospective follow-up study included 45 patients with confirmed COVID-19 admitted to a medical ward at the Montichiari Hospital, Brescia, Italy from November 2020 to April 2021 Patients had COVID-19 related pneumonia with respiratory failure and needed at least treatment with an inspired fraction of oxygen of 40% (of them, 59% were treated with Venturi mask and 41% needed non-invasive ventilation). Patients underwent a clinical assessment with standard laboratory testing, chest CT scan, lung function tests with DLCO, and evaluation of vital parameters after a mean of 382 days after hospital discharge. A quality-of-life questionnaire was administered to each willing patient. Results: See table for details. While standard laboratory testing showed a substantial normalization, we found persistence of radiological alterations (i.e. ground-glass opacities, irregular linear/reticular opacities) in 61% of patients; mean Tiffenau index (FEV1/FVC) was reduced, although not clearly pathologic (79%) and 38% of patients showed a mild to moderate reduction in CO lung diffusion (DLCO). Interestingly, 54% of subjects showed concomitant presence of radiologic alterations AND persistence of dyspnea OR reduction in CO lung diffusion, while 21% had all three concomitant conditions, compatible with the diagnosis of lung fibrosis. Overall, a total of 75% patients had some degree of functional or structural alteration of respiratory apparatus. We also evaluated quality of life thorough a structured questionnaire: after more than one year 62% of the patients still lamented fatigue, 62% effort dyspnea, 12% anorexia, 29% dysgeusia or anosmia, 31% insomnia and 43% anxiety. Conclusions: these data seem to demonstrate that SARS-CoV-2-related pneumonia requiring high flow oxygen has a heavy long-term burden, both in terms of persistence of functional and structural pulmonary damage (which may be progressive and evolve to a more severe degree) and of burden on overall quality daily life.